2009
DOI: 10.1093/carcin/bgp087
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between HSP60 and β-catenin promotes metastasis

Abstract: Heat shock protein 60 (HSP60) plays an essential role in assisting many newly synthesized proteins to reach their native forms. Increased HSP60 expression is observed in different types of human cancers with metastasis (e.g. pancreatic cancer and large bowel carcinoma). However, the role of HSP60 in metastasis remains little known. Aberrant activation of beta-catenin plays a key role in tumorigenesis and metastasis. Here, we show that overexpression of HSP60 induces metastatic phenotypes in vitro and in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 43 publications
3
76
0
2
Order By: Relevance
“…Indeed, loss of P-cadherin expression after PF-03732010 treatment resulted in decreased metastasis without any affect on the E-cadherin level, presumably, in part, due to the reduced tumor cell adhesiveness. More importantly, the antimetastatic activity was derived from the diminished level of β-catenin, which not only plays a functional role in stabilizing P-cadherin-mediated cell-cell adhesion but also regulates molecular signaling pathways to promote tumor growth, invasiveness, and metastasis (17,19). It has been shown that P-cadherin failed to induce invasion when the catenin-binding domain was mutated (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, loss of P-cadherin expression after PF-03732010 treatment resulted in decreased metastasis without any affect on the E-cadherin level, presumably, in part, due to the reduced tumor cell adhesiveness. More importantly, the antimetastatic activity was derived from the diminished level of β-catenin, which not only plays a functional role in stabilizing P-cadherin-mediated cell-cell adhesion but also regulates molecular signaling pathways to promote tumor growth, invasiveness, and metastasis (17,19). It has been shown that P-cadherin failed to induce invasion when the catenin-binding domain was mutated (38).…”
Section: Discussionmentioning
confidence: 99%
“…P-cadherin-associated tumor cell growth, motility, and invasiveness is likely or at least partially mediated by the relocalization of membrane β-catenin to the cytoplasm and subsequently into the nucleus where it partners with the T-cell factor and activates transcription of the target genes (14,17), including vimentin (18), cyclin D1, survivin, and BCL-2 (19). The upregulation of P-cadherin was frequently observed in various malignant tumors, including breast, colon, lung, and pancreatic tumors, and correlated with poor survival of breast cancer patients (15,20,21).…”
mentioning
confidence: 99%
“…Nuclear β-catenin is correlated with a poor prognosis in patients with metastasic HNSCC (Tsai et al, 2009). Rap1, a raslike protein, stabilized β-catenin and increased its nuclear localization; more advanced N-stage lesions were associated with high free β-catenin and high active Rap1 (Goto et al, 2010).…”
Section: β-Cateninmentioning
confidence: 99%
“…β-catenin is then translocated into the nucleus, where it binds to Tcf/Lef and initiates transcription of its target genes, which include c-myc; this results in cellular canceration (20,28). The β-catenin oncogenic protein is widely expressed in a number of human malignancies (29), including ESCC (30), head and neck squamous cell carcinoma (31)(32)(33) and colorectal cancer (34). Additionally, it has been reported that elevated β-catenin levels promote early neoplastic change through oncogenic signaling within cells (35,36).…”
Section: Discussionmentioning
confidence: 99%